Mechanical and Conductive Properties of Silicone Filled Graphene Electrically Conductive Adhesive (ECA) - Omar, Nurin Aisyah Ahmad; Baharudin, Adzrie; Rahman, Rozyanty; Yahya, Solhan; Ahmad, Zuliahani; Nawawi Wan Ismail, Wan Izhan (Archives of Metallurgy and Materials, 2026)
Electrically conductive adhesives (ECAs) are promising alternatives to traditional solders for flexible and lightweight electronic packaging. However, achieving high conductivity while maintaining good mechanical flexibility remains challenging. This study aims to develop a silicone-based graphene ECA modified with polyethylene glycol (PEG-600) to improve electrical and mechanical performance. Silicone/graphene ECAs were fabricated with varying graphene contents (0–9 wt.%) through controlled sonication and curing. The samples were characterized using tensile testing, Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), and Electrochemical Impedance Spectroscopy (EIS). FTIR spectra confirmed successful graphene incorporation through the presence of –OH, CH, C=C, and C=O functional groups, with the –OH peak shifting to higher intensity at 7% loading. Electrical conductivity reached an optimum of 4.87×10–6 S/cm at 9% graphene, attributed to the formation of continuous electron pathways within the polymer matrix. Mechanical tests revealed maximum tensile strength (0.305 MPa) and Young’s modulus (146.523 MPa) at 7% graphene before decreasing due to filler agglomeration. SEM analysis supported these findings with uniform filler dispersion at optimum loading. The synergistic addition of graphene and PEG-600 effectively enhanced conductivity and mechanical stiffness, demonstrating strong potential for flexible electronic applications.